THE NEW ETHIOPIAN HATE SPEECH AND DISINFORMATION PREVENTION PROCLAMATION: A Sign for Fracture of the Promises of the Reform? (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
This article studies the new Hate Speech and Disinformation prevention and suppression proclamation No. 1185/2020 that the government of Ethiopia endorsed recently. Contrary to the promises of Reform by Prime Minister Abiy Ahmed in 2018, the Law that has been ratified in 2020. The study employed the method of 'Qualitative Case study' with 'Evidence of Effect' and Realist approaches to the systematic review of literature on Ethiopian Reform and the procedures followed to ratify the draft Bill. It analyzed the draft bill document as a case study reflecting the current state of media freedom in Ethiopia. Supported by some key informant interviews, related literature on media pluralism, press freedom, news reports, and International Organizations such as Human Rights Watch and UNESCO on Hate Speech and Disinformation Proclamation are examined. The result shows that PM Abiy Ahmed has been very ambitious in early actions and decisions in the reform process. However, the internal political crises created polarization in the contents of various media and compelled the draft Law's ratification. The Document of the Proclamation Lacked Clarity in the definition of terms. As a result, it created misunderstandings in the implementation and justifications of the ratified proclamation, as disinformation is only one element of different types of misinformation. It is also unclear why the proclamation repealed the article it assumed to repeal in the Criminal Code of the Federal Democratic Republic of Ethiopia, while there are other related articles. Furthermore, the Law will suppress press freedom and media pluralism which are potential democratic ideals as the country is heading for a democratic political transition. Therefore, to minimize government indiscretion, policymakers must reexamine the substance and drafting of the Law to close the gaps. To cite this article (7th APA style): Eranfeno, G. N. (2022). The new Ethiopian hate speech and disinformation prevention proclamation:  A sign for fracture of the promises of the reform? Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 112-123. https://doi.org/10.36782/jcs.v12i2.2186